Does hyperthyroidism worsen prognosis of thyroid carcinoma? A retrospective analysis on 2820 consecutive thyroidectomies - Fabio Medas; Ernico Erdas; Gian Luigi Canu; Alessandro Longheu; Giuseppe Pisano; Massimiliano Tuveri; Pietro Giorgio Calò (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Hyperthyroidism is associated with high incidence of thyroid carcinoma; furthermore, tumors arisen in hyperthyroid tissue show an aggressive behavior. Thyroid Stimulating Hormone (TSH) and Thyroid-stimulating antibodies, present in Graves’s disease, seem to play a key role in carcinogenesis and tumoral growth. Methods We retrospectively reviewed our series of patients who underwent thyroidectomy for thyroid carcinoma. We compared pathological features and surgical outcomes of hyperthyroid versus euthyroid patients. Results From 2007 to 2015, 909 thyroidectomies were performed at our institution for thyroid cancer: 87 patients were hyperthyroid and 822 euthyroid. We observed, in hyperthyroid patients, a higher rate of transient hypoparathyroidism (28.1% vs 13.2%; p < 0.01) and of node metastases (12.6% vs 6.1%; p = 0.03); also local recurrence rate was higher (5.7% vs 2.5%) even if not statistically significant (p = 0.17). Five-year disease free survival rate was significant lower in the same group (89.1% vs 96.6%; p = 0.03). Conclusion Thyroid cancers in hyperthyroid patients have an aggressive behavior, with high incidence of local invasion and a worse prognosis than euthyroid patients. All hyperthyroid patients should undergo a careful evaluation with ultrasound and scintigraphy; in case of suspicious nodules, an aggressive approach, including thyroidectomy and lymphectomy, is justified. In patients with toxic adenoma, thyroid cancer is uncommon, thus a loboisthmectomy can be safely performed. Trial registration number Research registry n. 2670 registered 19 June 2017 (retrospectively registered).